Determinants Of Corporate Income Tax Payable With Operating Costs As Moderating Variable - Handayani, Rini; Endah Purnamasari Edhy (Jurnal Ekonomi, 2024)
The Covid-19 pandemic has had a negative impact around the world, including Indonesia, and has severely affected the health, economy, agriculture, and transportation sectors. Economic growth has declined since the second quarter of 2020, with a decline in corporate income and taxes received by the state. The decline in corporate income leads to a reduction in profits and corporate income taxes payable. This study aims to analyze the factors that affect corporate income tax in manufacturing companies before and after the pandemic. These factors include Profitability, Net Sales, Liquidity, and Leverage, as well as Operating Expenses as moderation variables. The study population includes all companies listed on the IDX, with a sample of manufacturing companies for the period 2019-2022. The data collection technique uses secondary data in the form of available financial statements. The analysis methods used are multiple linear regression and moderate regression analysis.